Avalanche photodiodes on silicon photonics. (1st February 2022) - Yuan, Yuan; Tossoun, Bassem; Huang, Zhihong; Zeng, Xiaoge; Kurczveil, Geza; Fiorentino, Marco; Liang, Di; Beausoleil, Raymond G.
Abstract: Silicon photonics technology has drawn significant interest due to its potential for compact and high-performance photonic integrated circuits. The Ge- or III–V material-based avalanche photodiodes integrated on silicon photonics provide ideal high sensitivity optical receivers for telecommunication wavelengths. Herein, the last advances of monolithic and heterogeneous avalanche photodiodes on silicon are reviewed, including different device structures and semiconductor systems.